Innovations in Quantitative Risk Management - Glau, Kathrin; Scherer, Matthias; Zagst, Rudi (Springer Proceedings in Mathematics & Statistics, 2015)
Quantitative Finance; Game Theory, Economics, Social and Behav. Sciences; Finance/Investment/Banking; Actuarial Sciences